Local Pulmonary Malformation Caused by Bilateral Coronary Artery and Bronchial Artery Fistulae to the Left Pulmonary Artery in a Patient with Coronary Artery Disease - Cijan, Andrej (2000)
At 10 years of age and again at 25, our patient had been treated for pulmonary tuberculosis due to the presence of a localized pulmonary shadow. Coronary angiography at age 59 revealed 3 fistulous communications: from the right and circumflex coronary arteries and from the left bronchial artery. All 3 emptied into the same recipient artery, the distal part of a left pulmonary artery branch, which produced substantial left-to-right shunt. On computed tomography, cystic formations could be seen in the pulmonic area. The pulmonary tuberculosis for which this patient had been treated in his youth was in the same part of the lung where the shunt was discovered. Our conclusion is that the initial diagnosis was in error.